Developmental pathways for social understanding: linking social cognition to social contexts - Brink, Kimberly A.; Lane, Jonathan D.; Wellman, Henry M. (Frontiers in Psychology, 2015)
Contemporary research, often with looking-time tasks, reveals that infants possess foundational understandings of their social worlds. However, few studies have examined how these early social cognitions relate to the child’s social interactions and behavior in early development. Does an early understanding of the social world relate to how an infant interacts with his or her parents? Do early social interactions along with social-cognitive understandings in infancy predict later preschool social competencies? In the current paper, we propose a theory in which children’s later social behaviors and their understanding of the social world depend on the integration of early social understanding and experiences in infancy. We review several of our studies, as well as other research, that directly examine the pathways between these competencies to support a hypothesized network of relations between social-cognitive development and social-interactive behaviors in the development from infancy to childhood. In total, these findings reveal differences in infant social competences that both track the developmental trajectory of infants’ understanding of people over the first years of life and provide external validation for the large body of social-cognitive findings emerging from laboratory looking-time paradigms.